STUDI LITERATUR TENTANG FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS AUDIT - Anselmus Rufus Kodu; Carmel Meiden (HelFin Journal, 2024)
This study aims to conduct a literature review on audit quality in the context of various previous studies. Audit quality is a crucial aspect in ensuring the integrity and trustworthiness of an organization's financial statements. This literature review investigates various factors influencing audit quality, such as Audit Fee, Audit Tenure, Audit Rotation, Independence, and Competence. The Systematic Literature Review (SLR) method is utilized to explore research evidence related to audit quality from 2021 to 2023, involving the analysis of a total of 22 selected articles. The analysis results indicate that Audit Fee, Audit Tenure, Audit Rotation, Independence, Code of Ethics, and Competence are the most frequently discussed factors in the literature. Specifically, the Code of Ethics is considered to have a significant influence on audit quality. However, there is debate regarding the significance of other variables such as Audit Fee, Audit Tenure, and Audit Rotation. The implications of this literature review underscore the importance of considering the aforementioned factors, such as Audit Fee, Audit Tenure, Audit Rotation, Independence, Competence, and Code of Ethics, in ensuring optimal audit quality.